An in vitro scanning electron microscopic study: smear layer removal by chelat activation methods - Le, Thi Thu Nga; Phan, Anh Chi (Tạp chí Y Dược Huế, 2022)
Background: The process of mechanical root canal preparation creates smear layer. The smear layer can prevent the penetration of intracanal medicaments into dentinal tubules and influence the adaptation of filling materials to canal walls. The purpose of this study is to compare the smear layer removal ability of root canal irrigation methods with chelat solution. Materials and Methods: 45 extracted human premolar roots were selected and randomly divided into 3 groups (n=15) based on root canal irrigation methods with 17% EDTA solution: (1) Conventional needle irrigation, (2) Ultrasonic activation, (3) Sonic activation. The roots were prepared with Reciproc Blue 25 file and was removed smear layer by 3 different methods of irrigation. The study sample was then sectioned longitudinally with a diamond cutting disc, randomly selecting half of the root. After undergoing sample processing, the half roots were observed and evaluated for the presence of smear layer under a scanning electron microscope with a magnification of 1000 times according to Torabinejad (2003). Results: In cervical, the average smear layer score of the 3 study groups was not statistically significant (p>0.05). In the middle, apical and over the root canal, the average smear layer score of the sonic activation method was lower than that of the other 2 groups. Conclusion: Sonic irrigation is more effective in removing smear layer than conventional needle irrigation and ultrasonic irrigation activation.